Delayed bracket placement in orthodontic treatment - Chandra Wigati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Beside bracket position, the timing of bracket placement is one of the most essential in orthodontic treatment with fixed appliances. Even it seems simple the timing of bracket placement can be crucial and significantly influence the result of orthodontic treatment. However it is often found brackets are placed without complete understanding of its purpose and effects, which could be useless and even detrimental for the case. Purpose: The aim of this case report is to show that the timing of bracket placement could be different depending on the cases. Case: Five different cases are presented here with different timing of bracket placement. Case management: On these cases, brackets were placed on the upper arch first, on the lower arch first, or even only on some teeth first. Good and efficient orthodontic treatment results were achieved. Conclusion: For every orthodontic case, from the very beginning of treatment, bracket should be placed with the end result in mind. If brackets are correctly placed at a correct time, better treatment result could be achieved without unnecessary round tripping tooth movement.